Temporal Measurements of Deglutition in Dynamic Magnetic Resonance Imaging versus Videofluoroscopy. (December 2013) - Lafer, Marissa; Achlatis, Stratos; Lazarus, Cathy; Fang, Yixin; Branski, Ryan C.; Amin, Milan R.
Objectives: We undertook to provide data regarding temporal measurements of swallow function obtained by dynamic magnetic resonance imaging in a midsagittal plane and to compare these values to normative fluoroscopy data. Methods: Seventeen healthy female volunteers with no swallowing complaints underwent turbo-fast low-angle-shot magnetic resonance imaging with a 3-T scanner while swallowing liquid and pudding boluses delivered via syringe. Ninety sequential images were acquired with a temporal resolution of 113 ms per frame for each swallow. The imaging was performed in the midsagittal plane. The analyses focused on oral and pharyngeal transit times. Results: All subjects tolerated the protocol without complaints or adverse events. The mean (±SD) oral transit times for liquids and pudding were measured as 0.25 ± 0.09 second and 0.25 ± 0.13 second, respectively. This difference was not statistically significant (p = 0.74). The mean pharyngeal transit times for liquids and pudding were measured as 0.84 ± 0.16 second and 1.11 ± 0.21 seconds, respectively. This difference achieved statistical significance (p < 0.0001). The intrarater and inter-rater reliabilities for the measurements were excellent. Conclusions: This sequence provided a high degree of temporal resolution of deglutition in the midsagittal plane. Furthermore, the temporal measurements acquired with dynamic magnetic resonance imaging were reliable and were relatively consistent with those of previous studies done with videofluoroscopy.